Upaya USAID Dalam Membantu Mewujudkan Perikanan Berkelanjutan di Indonesia tahun 2016-2021 - Vidiana, Louisia; Dewi, Putu Ratih Kumala; Nugraha, Anak Agung Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
IUU Fishing is one of the biggest obstacles to fully utilizing Indonesia’s fishery potential and the government’s goal to implement sustainable fisheries management. WPP-NRI 715 is selected as the main focus as it has the strategic position of being in the Coral Triangle area, high level of IUU fishing, and the value of the utilization rate, which on average was in the over-exploited category. This study used a descriptive qualitative method to describe USAID's efforts in helping the Indonesian government to actualize sustainable fisheries management using data collected through secondary analysis. The result of the analysis, using the concepts of foreign aid, blue economy, and sustainable fishery, showed that USAID tried to develop the USAID SEA program by aligning it with the main focus of the Indonesian government to implement the blue economy in the marine and fisheries sector. USAID SEA project is carrying out several programs: implementing EAFM, developing MPA and MPA networks, marine spatial planning, law enforcement, increasing awareness through the formation of SEA Champions, and establishing marine governance incentives through the implementation of Fair Trade.